An Effective Implementation of Environmental Science Course at Undergraduate Level - Ramu, , Sridarala (International Journal of Psychosocial Rehabilitation, 2020)
-- Environmental science connects with any issue that influence surrounding and living organism. Environmental sciences is a multidisciplinary subject. Obeying the supreme court of India orders in the year 1999 environmental science course has been made mandatory for all undergraduates including engineering students. The chief cause of implementing this course is to bring awareness on environment, to reduce environmental pollution and to save environment. Many researchers proved that environmental education will develop pro environmental behavior and environment friendly thinking. Multiple studies proved that persons with higher environment knowledge follow the principle Reduce, Reuse and Recycle. Even though Supreme Court ordered to implement this course more effectively, this course is not attaining much importance in engineering programme. There is a significant gap between Environmental science course and engineering core subjects. To find out the reasons for this gap a research was conducted and presented in this paper. In the present investigation a questionnaire was prepared and distributed to the students to take opinions from the students. Data collected from 600 students from different branches. Results of present investigation proved the importance of the environmental science course, modification of syllabus, necessity to give credits to Environmental science course. This research also proved the role of Environmental science course to make India “Clean India” (Swachh Bharat).